(+)-Usnic Acid Inhibits Migration of c-KIT Positive Cells in Human Colorectal Cancer. (12th September 2018) - Wu, Wei; Hou, Bing; Tang, Changli; Liu, Fucheng; Yang, Jie; Pan, Tao; Si, Ke; Lu, Deyun; Wang, Xiaoxiang; Wang, Jing; Xiong, Xing; Liu, Ji; et al.
Abstract : Inhibition of tumor cell migration is a treatment strategy for patients with colorectal cancer (CRC). SCF-dependent activation of c-KIT is responsible for migration of c-KIT positive [c-KIT(+)] cells of CRC. Drug resistance to Imatinib Mesylate (c-KIT inhibitor) has emerged. Inhibition of mTOR can induce autophagic degradation of c-KIT. (+)-usnic acid [(+)-UA], isolated from lichens, has two major functions including induction of proton shuttle and targeting inhibition of mTOR. To reduce hepatotoxicity, the treatment concentration of (+)-UA should be lower than 10 μ M. HCT116 cells and LS174 cells were employed to investigate the inhibiting effect of (+)-UA (<10 μ M) on SCF-mediated migration of c-KIT(+) CRC cells. HCT116 cells were employed to investigate the molecular mechanisms. The results indicated that firstly, 8 μ M (+)-UA decreased ATP content via uncoupling; secondly, 8 μ M (+)-UA induced mTOR inhibition, thereby mediated activation suppression of PKC-A, and induced the autophagy of the completed autophagic flux that resulted in the autophagic degradation and transcriptional inhibition of c-KIT and the increase in LDH release; ultimately, 8 μ M (+)-UA inhibited SCF-mediated migration of CRC c-KIT(+) cells. Taken together, 8 μ M could be determined as the effective concentration for (+)-UA to inhibit SCF-mediated migration of CRC c-KIT(+) cells.